6(3x-6)=3(6x+4)

Simple and best practice solution for 6(3x-6)=3(6x+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(3x-6)=3(6x+4) equation:


Simplifying
6(3x + -6) = 3(6x + 4)

Reorder the terms:
6(-6 + 3x) = 3(6x + 4)
(-6 * 6 + 3x * 6) = 3(6x + 4)
(-36 + 18x) = 3(6x + 4)

Reorder the terms:
-36 + 18x = 3(4 + 6x)
-36 + 18x = (4 * 3 + 6x * 3)
-36 + 18x = (12 + 18x)

Add '-18x' to each side of the equation.
-36 + 18x + -18x = 12 + 18x + -18x

Combine like terms: 18x + -18x = 0
-36 + 0 = 12 + 18x + -18x
-36 = 12 + 18x + -18x

Combine like terms: 18x + -18x = 0
-36 = 12 + 0
-36 = 12

Solving
-36 = 12

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 2x+3(4)=2 | | 2x+3(3.25)=2 | | 2x+3(4.5)=2 | | 2x+3(2.5)=2 | | 2x+3(6.8)=2 | | x(3x+2)-5=0 | | -4-7x+5x=-2 | | 14x^2-196x+686=0 | | 2x+(-2x-6)=5 | | 3.50x=40.00 | | 3x^2-22x+84=0 | | y+156.19=25.4523-30.024 | | 3/44=x/12 | | 3x^2+22x+84=0 | | 44/3=x/12 | | 6n^2-55=-7n | | 3k^2+3k=18 | | r/3=27 | | 12-6=9x+12 | | 3k^2+3k=0 | | 4/3=x/21 | | Z-201/7=6 | | (-3-5(-2))/(-7-2(-3)) | | ax^2+10x-5=0 | | 1/2=-5/7+f | | 4v^2=6 | | .14(y-7)+.12y=.20y-0.05(10) | | x+2x+3x+25x=95 | | 46/7a=212/7 | | 10x^2=2x-6 | | 3/4=h+1/6 | | 135/6+d=125/8 |

Equations solver categories